The genetic basis of tooth agenesis: Basic concepts and genes involved - Sharat Chandra Pani (Wolters Kluwer Medknow Publications, 2011)
Tooth agenesis is the most prevalent craniofacial congenital malformation in humans. While tooth agenesis may be associated with several syndromes, non-syndromic hypodontia refers to the congenital absence of a few teeth in the absence of any other deformity. Recent advances in molecular genetics have made it possible to identify the exact genes responsible for the development of teeth and trace the mutations that cause hypodontia. This paper reviews the literature regarding the genetic basis of non-syndromic tooth agenesis, methods used to study it, and the genes that have been definitively implicated in the agenesis of human dentition.